Relations Between State Institutions in Indonesia after the Amendment to the 1945 Constitution - Sarkawi, (International Journal of Scientific Research and Management (IJSRM), 2023)
Amendments to the 1945 Constitution resulted in changes to state institutions. This is due to changes in the provisions governing state institutions. Some fundamental principles that determine relations between state institutions include the Supremacy of the Constitution, the Presidential System, and the Separation of Powers and Checks and Balances. Based on the description of the discussion in this article, it is concluded that the relationship between state institutions in Indonesia includes: (1) Relations between State Institutions in the Field of Government; (2) Relations Between State Institutions in the field of Legislation; (3) Relations Between State Institutions in the Judicial Sector, namely; (a) Relations between the Supreme Court and the Constitutional Court; (b) Relations between the Supreme Court and the President; (c) Relations between the Supreme Court and the House of Representatives.